2020
DOI: 10.3390/pr8091194
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II) and As(V) Adsorption Kinetic Characteristic of the Multifunctional Amino Groups in Chitosan

Abstract: Amino groups in the chitosan polymer play as a functional group for the removal of cations and anions depending on the degree of protonation, which is determined by the solution pH. A hydrogel beadlike porous adsorbent was used to investigate the functions and adsorption mechanism of the amino groups by removal of Cu(II) as a cation and As(V) as an anion for a single and mixed solution. The uptakes of Cu(II) and As(V) were 5.2 and 5.6 μmol/g for the single solution and 5.9 and 3.6 μmol/g for the mixed solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 54 publications
(67 reference statements)
1
33
0
1
Order By: Relevance
“…The very good linearity of the q t = f(t 1/2 ) plots is highlighted by the values of the coefficients of determination over 0.95, confirming the applicability of the intraparticle diffusion model to describe the ions dissolution. This behavior, previously mentioned in literature [49,50], indicates that two processes influence the ion leaching in the citric acid solution. The first corresponds to the diffusion through the vitreous matrix and the second to the diffusion through the glass particle-medium interface.…”
Section: Chemical Activitysupporting
confidence: 73%
“…The very good linearity of the q t = f(t 1/2 ) plots is highlighted by the values of the coefficients of determination over 0.95, confirming the applicability of the intraparticle diffusion model to describe the ions dissolution. This behavior, previously mentioned in literature [49,50], indicates that two processes influence the ion leaching in the citric acid solution. The first corresponds to the diffusion through the vitreous matrix and the second to the diffusion through the glass particle-medium interface.…”
Section: Chemical Activitysupporting
confidence: 73%
“…As shown in (Figure c) and Table , the R 2 value of the Weber and Morris intraparticle diffusion model was low and the regression line does not pass through the origin. Instead, two different segments of the curve could be related to the driving of adsorption diffusion by both the film and intraparticle diffusion …”
Section: Resultsmentioning
confidence: 99%
“…Instead, two different segments of the curve could be related to the driving of adsorption diffusion by both the film and intraparticle diffusion. 61 2.5. Continuous Fixed-Bed Adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the film-diffusion step was the slowest step during TGCN adsorption. These findings indicated that TGCN has a higher affinity toward the CRNPs surface than the other three drugs and implied the significance of pore-diffusion in removing DXCN, CTCN, and OTCN [ 78 ].…”
Section: Resultsmentioning
confidence: 99%